Dinamika Solidaritas Mekanis dan Solidaritas Organik dalam Manajemen Pendidikan: Perspektif Durkheimian - Dina Sri Mulyani; Silfia Hanani; Aisyah Syafitri; Indra Devi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
Understanding mechanical and organic solidarity theories, education management can utilise these insights to design an effective, inclusive and relevant education system in the face of continuous social and technological change. The purpose of this research is to explain the Dynamics of Mechanical Solidarity and Organic Solidarity in Education Management: A Durkheimian Perspective. The method used in this study uses qualitative research procedures using a research approach in the form of a literature study. The sources of information in this study were reviewed from various novel sources of literature, research reports, essays, theses, dissertations and posts both print and electronic related to the Dynamics of Mechanical Solidarity and Organic Solidarity in Education Management: A Durkheimian Perspective. The results of this study show that education management should be able to create the right balance between these two types of solidarity. This means understanding the importance of maintaining valuable social norms while accommodating individual diversity. In a modern society, education management should allow students to grow according to their potential, enable student participation in decision-making, encourage collaboration between stakeholders, and respond with flexibility to social change.